The distribution of economic resources to children in Germany - Maximilian Stockhausen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2017)
This paper investigates the redistributive impact of private and public childcare provision and education on children's resources in Germany between 2009 and 2013. It takes account of the multidimensionality of children's needs and access to economic resources by applying an extended income approach. Combining survey data from the Socio-Economic Panel (SOEP) with administrative data from the German Federal Statistical Office, extended disposable income inequality is found to be significantly lower than disposable cash income inequality at the five percent level across all years. However, the extension does not significantly change distributional trends. At the same time, publicly provided childcare and schooling notably decrease inequality among children such that it cushions cash income inequality. One major reason for this effect is that public in-kind benefits profit children living with single parents, which are deprived in terms of cash incomes, most. This gives additional evidence on the importance of publicly provided childcare and schooling as a policy instrument to equalize economic resources and opportunities in children's lives.
Keywords: D13; D31; H52; I24; 330; in-kind benefits; opportunity costs; non-cash incomes; extended income; economic inequality